Evaluating tree frog habitat use in a montane wetland using tree tube shelters - Aleen Ammar (UNC Test Journal, 2024)
Ephemeral wetlands are breeding sites for a variety of amphibian species. When human activity and development are adjacent to these environments, it is crucial to consistently monitor the aquatic-breeding species so changes in biodiversity and species richness due to season, weather, and species competition can be distinguished from human-associated changes. This study establishes a sampling protocol for quantifying the abundance and habitat use of Cope’s gray tree frogs (Hyla chrysoscelis) and the spring peeper (Pseudacris crucifer) within a montane wetland in western North Carolina. These species have been documented at the site, but have not been monitored systematically. We monitored biweekly, from August to March, an array of 40 PVC pipes, placed on trees throughout the wetland along vernal pools, as a means of determining tree frog habitat use. Beginning in January, we also conducted calling surveys for breeding spring peepers and pond sampling for larvae to evaluate the ability of our tubes to detect these species when they were present. My goal was to use this combined approach to quantify relative abundance throughout the pre- to post-breeding seasons and their distribution at this site throughout the environment. I found that although the tree tubes were not used by spring peepers, they were in the area and calling. Further, the pond sampling detected adult and larval salamanders, but not larval spring peepers. The presence of calling adults aligns with our previous notions of spring peeper presence in the wetland, however lack of usage in the refugia could be due to low density early in the breeding season. This means that continued monitoring is important to catch any activity from spring peepers and Cope’s gray treefrogs.